RAINBOW CONNECTION PADA GRAF k -CONNECTED UNTUK k = 1 ATAU 2 - Sally Marhelina (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
An edge-colored graph G is rainbow connected if any two vertices are connected by a path whose edges have distinct colors. The rainbow connection number of aconnected graph G, denoted by rc(G) is the smallest number of colors needed such thatG is rainbow connected. In this paper, we will proved again that rc(G) ≤ 3(n + 1)/5 forall 3-connected graphs, and rc(G) ≤ 2n/3 for all 2-connected graphs.